Melanopsin as a sleep modulator: circadian gating of the direct effects of light on sleep and altered sleep homeostasis in Opn4(-/-) mice. - Jessica W Tsai (Public Library of Science (PLoS), 2009)
Light influences sleep and alertness either indirectly through a well-characterized circadian pathway or directly through yet poorly understood mechanisms. Melanopsin (Opn4) is a retinal photopigment crucial for conveying nonvisual light information to the brain. Through extensive characterization of sleep and the electrocorticogram (ECoG) in melanopsin-deficient (Opn4(-/-)) mice under various light-dark (LD) schedules, we assessed the role of melanopsin in mediating the effects of light on sleep and ECoG activity. In control mice, a light pulse given during the habitual dark period readily induced sleep, whereas a dark pulse given during the habitual light period induced waking with pronounced theta (7-10 Hz) and gamma (40-70 Hz) activity, the ECoG correlates of alertness. In contrast, light failed to induce sleep in Opn4(-/-) mice, and the dark-pulse-induced increase in theta and gamma activity was delayed. A 24-h recording under a LD 1-hratio1-h schedule revealed that the failure to respond to light in Opn4(-/-) mice was restricted to the subjective dark period. Light induced c-Fos immunoreactivity in the suprachiasmatic nuclei (SCN) and in sleep-active ventrolateral preoptic (VLPO) neurons was importantly reduced in Opn4(-/-) mice, implicating both sleep-regulatory structures in the melanopsin-mediated effects of light. In addition to these acute light effects, Opn4(-/-) mice slept 1 h less during the 12-h light period of a LD 12ratio12 schedule owing to a lengthening of waking bouts. Despite this reduction in sleep time, ECoG delta power, a marker of sleep need, was decreased in Opn4(-/-) mice for most of the (subjective) dark period. Delta power reached after a 6-h sleep deprivation was similarly reduced in Opn4(-/-) mice. In mice, melanopsin's contribution to the direct effects of light on sleep is limited to the dark or active period, suggesting that at this circadian phase, melanopsin compensates for circadian variations in the photo sensitivity of other light-encoding pathways such as rod and cones. Our study, furthermore, demonstrates that lack of melanopsin alters sleep homeostasis. These findings call for a reevaluation of the role of light on mammalian physiology and behavior.